2018
DOI: 10.21037/atm.2018.06.21
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria and cardiovascular diseases—from pathophysiology to treatment

Abstract: Mitochondria are the source of cellular energy production and are present in different types of cells. However, their function is especially important for the heart due to the high demands in energy which is achieved through oxidative phosphorylation. Mitochondria form large networks which regulate metabolism and the optimal function is achieved through the balance between mitochondrial fusion and mitochondrial fission. Moreover, mitochondrial function is upon quality control via the process of mitophagy which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
145
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(152 citation statements)
references
References 221 publications
(231 reference statements)
5
145
0
2
Order By: Relevance
“…It has been shown that endothelial mitochondria play a prominent role in the pathophysiology of atherosclerosis. Mitochondrial dysfunction results in excessive production of ROS, which oxidize mitochondrial components, including mitochondrial DNA, proteins, and lipids, and further exacerbate ROS generation and set up a vicious cycle, thereby contributing to atherosclerosis (40, 41). Because alteration of MMP is a risk factor that drives excess mitochondrial ROS production, we measured the effects of lunasin on MMP to estimate the influence of lunasin on mitochondrial function in EA.hy926 cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that endothelial mitochondria play a prominent role in the pathophysiology of atherosclerosis. Mitochondrial dysfunction results in excessive production of ROS, which oxidize mitochondrial components, including mitochondrial DNA, proteins, and lipids, and further exacerbate ROS generation and set up a vicious cycle, thereby contributing to atherosclerosis (40, 41). Because alteration of MMP is a risk factor that drives excess mitochondrial ROS production, we measured the effects of lunasin on MMP to estimate the influence of lunasin on mitochondrial function in EA.hy926 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) are commonly defined as a class of small and highly reactive chemical species resulting from incomplete one-electron reduction of oxygen (e.g., superoxide, hydroxyl radicals, and peroxides such as hydrogen peroxide) [1,2]. In physiological settings, ROS are produced through both non-enzymatic and enzyme-catalyzed reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Cellular ROS are commonly generated through mitochondrial respiratory chain in most tissues. Steady-state ROS are maintained at nontoxic levels through various antioxidant and repair enzymes [2,5,6]. The delicate balance between oxidative stress and antioxidant defenses appears to play an essential role in cell survival, proliferation, and cell death [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations